Evaluation of the readiness level in project portfolio management: Case study of the Public Security Department of the State of Bahia - Brazil (Research, Society and Development, 2021)
This paper analyzes the degree of readiness in project portfolio management at the Public Security Secretariat of the State of Bahia, Brazil. The study used the PPM Ready model (Project portfolio management ready) proposed by Norberto Almeida. This model analyzes the degree of readiness in project portfolio management through three steps, evaluating four pillars. Organizations are structured by their continuous operations and projects, which are the means by which an idea is transformed into a tangible product, service or solution. But the level they use and are aware of project portfolio management varies. Further maturing in project portfolio management provides lower-than-expected costs, shorter deadlines with successful project closure. The more mature an organization is, the higher the success rate of its projects. To reach maturity, there is a continuous effort that usually takes a few years before the results achieved reflect a higher rate of success in the results of the projects. Several project management maturity assessment models have been created to see how much organizations are doing to improve their performance. Most of them evaluate the level of project management and there is a lack of other levels, such as portfolio management. The assessment of maturity in organizations that have implemented portfolio management is a very recent topic and has not been discussed in depth in academia, especially in the public sector.